Automated Visual Inspection and Machine Vision IV 2021
DOI: 10.1117/12.2592872
|View full text |Cite
|
Sign up to set email alerts
|

Automated visual inspection of fabric image using deep learning approach for defect detection

Abstract: As a popular topic in automation, fabric defect detection is a necessary and essential step of quality control in the textile manufacturing industry. The main challenge for automatically detecting fabric damage, in most cases, is the complex structure of the textile. This article presents a two-stage approach, combining novel and traditional algorithms to enhance image enhancement and defect detection. The first stage is a new combined local and global transform domain-based image enhancement algorithm using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The general scheme of the proposed method is shown in Figure 4. For image enhancement we combined local and global transform based on multi-scale block-rooting processing [1,2].…”
Section: The Defect Detection Methodsmentioning
confidence: 99%
“…The general scheme of the proposed method is shown in Figure 4. For image enhancement we combined local and global transform based on multi-scale block-rooting processing [1,2].…”
Section: The Defect Detection Methodsmentioning
confidence: 99%
“…Traditional algorithms are based on the design of previously known functions based on spectral, structural, statistical, model approaches [4]. Some methods can be based on the use of Gabor filters [5], wavelet transforms [6], Fourier transforms [7], texture descriptors [8], etc.…”
Section: Related Workmentioning
confidence: 99%
“…Inspection of fabric materials by a person has low efficiency, individual differences, and it takes time to train a specialist. Experimental studies conducted in [3] showed that a person can recognize only 50-70% of all fabric defects [4]. In most cases, the inspection of fabric materials is carried out already at the final stage of production.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons with the other works found in the scientific literature (e.g. [6], [7], [8], [9], [10], and [11]) cannot be directly made, inasmuch as this module focuses in the detection of defects, rather than…”
Section: 𝐴𝑐𝑐𝑢𝑟𝑎𝑐𝑦 = 𝑇𝑃+𝑇𝑁 𝑇𝑃+𝑇𝑁+𝐹𝑃+𝐹𝑁mentioning
confidence: 99%
“…Accuracies between 99.16% and 77.13% were obtained. Another work that combines traditional and novel algorithms was proposed in [11], more specifically, digital image processing for visual data enhancement and neural networks for fabric defects detection. In most of the works found in literature, validations are carried out with datasets of fabric/leather defects, such as TILDA [12] and MVTec AD [13].…”
Section: Introductionmentioning
confidence: 99%